Structural, functional properties and in vitro digestibiligy of maize starch under heat-moisture and atmospheric-cold plasma treatments - Trinh , Khanh Son; Nguyen , Thuy Linh (Vietnam Journal of Science and Technology, 2018)
Maize starch is one of an important material which widely using in food applications and other industries. However, natural properties of raw starch can not be suitable for processed foods. So, the modification of starch is very important. In this study, heat-moisture and atmospheric cold argon-plasma treatments were applied in maize starch; then, structural, fuctional properties and digestibility of modified starch was investigated. Raw starch was heated at 20, 25 and 30% of moisture content. Subsequently, sample was treated under argon-plasma environment at fixed paramentes (137,5 V; 1.0 A for 10 min). Sample was investigated degree of cross-linking, degree of relative crystallinity (DRC), degree of hydrolysis using alpha-amylase, in vitro digestibility, changes in the hydration properties such as water absorbance index, swelling factor and water solubility index. Results show that degree of cross-linking, DRC, resistant starch of samples significantly increase under heat-moisture and plasma treatments; especially, sample of 20% heat-moisture contains 3-folded to 10-folded increase comparing to raw starch base on with or without pre-boiling process. Furthermore, water absorbance index and swelling factor decrease but water solubility index increase under plasma treatment.